Facebook Live through Zoom as Alternative Online Learning Media During COVID-19 Pandemic - Vertygo, Stormy (Bulletin of Social Studies and Community Development, 2023)
Abstract: Facebook Live through ZOOM as Alternative Online Learning Media During the COVID-19 Pandemic. Purpose: to evaluate the use of Facebook Live through ZOOM as an alternative online learning media during the COVID-19 pandemic. Methods: A survey in the form of a Google form was given to 254 student respondents whose data was further supported through interviews and student assignment scores. Further data analysis followed the procedure of Miles, Huberman, and Saldana (2013). Findings: Most students of Politani Kupang recommend using Facebook Live via ZOOM because it is easy to use, low on packet and does not require a very fast network connection. Conclusion: Facebook live through ZOOM can be used as an alternative online learning media in accordance with the characteristics of students who have limited network connections and internet data packages. Keywords: facebook live, zoom, online learning media, covid-19 pandemic